Converting TREx-RGB green-channel data to 557.7 nm auroral intensity: Methodology and initial results - Jun Liang; D. M. Gillies; E. Spanswick; E. F. Donovan (Earth and Planetary Physics, 2024)
The recently deployed Transition Region Explorer (TREx)-RGB (red-green-blue) all-sky imager (ASI) is designed to capture “true color” images of the aurora and airglow. Because the 557.7 nm green line is usually the brightest emission line in visible auroras, the green channel of a TREx-RGB camera is usually dominated by the 557.7 nm emission. Under this rationale, the TREx mission does not include a specific 557.7 nm imager and is designed to use the RGB green-channel data as a proxy for the 557.7 nm aurora. In this study, we present an initial effort to establish the conversion ratio or formula linking the RGB green-channel data to the absolute intensity of 557.7 nm auroras, which is crucial for quantitative uses of the RGB data. We illustrate two approaches: (1) through a comparison with the collocated measurement of green-line auroras from the TREx spectrograph, and (2) through a comparison with the modeled green-line intensity according to realistic electron precipitation flux measurements from low-Earth-orbit satellites, with the aid of an auroral transport model. We demonstrate the procedures and provide initial results for the TREx-RGB ASIs at the Rabbit Lake and Lucky Lake stations. The RGB response is found to be nonlinear. Empirical conversion ratios or formulas between RGB green-channel data and the green-line auroral intensity are given and can be applied immediately by TREx-RGB data users. The methodology established in this study will also be applicable to the upcoming SMILE ASI mission, which will adopt a similar RGB camera system in its deployment.